Resource potential of bamboo, challenges and future directions towards sustainable management and utilization in Ethiopia - Desalegn, Getachew; Tadesse, Wubalem (Forest Systems, 2014)
Aim of study: Bamboo, the fastest growing and high yielding perennial plant of the world has more than 1500 species and 1500 versatile socio-economic uses and ecological services. Ethiopia has two indigenous bamboo species namely Yushania alpina and Oxytenantheria abyssinica, covering about one million ha with a wide distribution. The objective of this paper is to highlight the potential of bamboo resources, challenges including biodeterioration damage, opportunities and future research directions towards its sustainable management and rational utilization. Area of study: Bamboo resources of Ethiopia Material and Methods: Reconnaissance survey was done to some parts of the bamboo growing potential areas in Ethiopia besides the literature review. Main results: The bamboo resource, despite its socio-economic and environmental benefits, currently, in most areas has been under high pressure due to land use changes, bamboo mass- flowering, poor processing with low value addition, and damage by biodeteriorating agents (termites, beetles and fungi). The preservative tests on Ethiopian bamboos revealed low natural durability and highlighted the paramount importance of appropriate protection measures such as Tanalith and vehicles used motor oil to increase durability, service life and rational utilization of bamboo-based products and structures as potential alternative construction and furniture material. Research highlights: Therefore, integrated research and development interventions involving different propagation and managements techniques, harvesting season, processing, value addition including proper seasoning and preservation technologies and marketing are recommended to fill the information and technological gaps on sustainable management and rational utilization of this fast growing and multipurpose bamboo resources in Ethiopia. Key words: Bamboo; challenges; management; socio-economic and environmental significance; utilization.